Developing digital marketing : relationship perspectives - Thaichon, Park; Ratten, Vanessa (Bingley, U.K. : Emerald Publishing Limited, 2021)
Digital marketing has gained ascendancy as the modern communication method used by most organizations through its ability to transcend geographic restrictions. Developing Digital Marketing: Relationship Perspectives provides a holistic perspective about the role of digital marketing in the global economy. Each chapter offers a different perspective about the importance of digital marketing in the knowledge economy, helping readers to understand the shift from traditional marketing to more novel and innovative forms that are derived from digital marketing functions. Themes explored throughout the book include: Service Encounters via Social Media and Customer Relationships; Digital and Organizational Storytelling; Artificial Intelligence and Customer Experience; Sustainability Project Partnerships. As the nature of these digital practices is evolving Developing Digital Marketing: Relationship Perspectives views the concept of digital marketing as now in constant flux, with the edited chapters paving the way to a better appreciation of how digital marketing is changing particularly through issues such as environmental sustainability in the current business environment.
chapter 1. The development and current trends of digital marketing and relationship perspectives in marketing research / Dung Le, Tuyet-Mai Nguyen, Sara Quach, Park Thaichon, and Vanessa Ratten -- chapter 2. Abandonment issues : why consumers abandon online shopping carts / Pemika Rochanapon, Michelle Stankovic, Matthew Barbera, Billy Sung, and Sean Lee -- chapter 3. Digital marketing and social entrepreneurship in Vietnam / Ngoc Le and Vanessa Ratten -- chapter 4. Digital marketing and geopolitical uncertainty in banking portfolio management : evidence for China commercial banks / Lazaros Ntasis, Christos E. Kountzakis, Konstantinos Koronios, Panagiotis E. Dimitropoulos, and Vanessa Ratten -- chapter 5. Digital sport marketing / Vanessa Ratten and Ashleigh-Jane Thompson -- chapter 6. Entrepreneurship education and digital marketing : what does the future hold? / Vanessa Ratten and Sumayya Rashid -- chapter 7. Are we already living with Skynet? : anthropomorphic artificial intelligence to enhance customer experience / Rakibul Hasan, Park Thaichon, and Scott Weaven -- chapter 8. Blurring the line between physical and digital environment : the impact of artificial intelligence on customers' relationship and customer experience / Rakibul Hasan, Scott Weaven, and Park Thaichon -- chapter 9. An analysis of subliminal static images and words using eye tracking techniques / Anish Babu Zacharia and Nicolas Hamelin -- chapter 10. Igniting the flame with electronic word-of-mouth in digital marketing / Yi Bu, Park Thaichon, and Joy Parkinson -- chapter 11. The current trends and future direction of digital marketing and relationship perspectives in business practice / Tuyet-Mai Nguyen, Dung Le, Sara Quach, Park Thaichon, and Vanessa Ratten.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Internet marketing; Computers, Internet -- General; Internet: general works